Determination of Total Phenolic and Caffeine Content and Their Correlation with Antioxidant Activity in Local Coffee Brews from South Kalimantan - Nashrul Wathan; Naura Azmira; Nurul Khasanah Anaini; Nur Aulia Yahya; Dhian Ririn Lestari; Joharman Joharman; Fadlilaturrahmah Fadlilaturrahmah (Universitas Lambung Mangkurat, 2026)
Coffee brews are widely consumed beverages known to contain bioactive compounds such as phenolic compounds and caffeine that provide health benefits, including antioxidant activity. The objective of this research is to evaluate the antioxidant activity, total phenolic content, and caffeine content of coffee brews made from local coffee beans of South Kalimantan, demonstrating their potential as functional beverages with health promoting properties. The local coffee beans used in this study originated from Pengaron, Aranio, Mataraman and Bati-Bati. The research included sample identification, beverage formulation, antioxidant activity assay using the DPPH method, and analysis of total phenolic and caffeine content using UV-Vis spectrophotometry. The results showed that the antioxidant activity, as indicated by IC₅₀ values, was lowest in coffee from Pengaron (202.962 ± 0.89 ppm), followed by Aranio (166.716 ± 0.358 ppm), Mataraman (150.043 ± 0.345 ppm), and the strongest in Bati-Bati (113.242 ± 0.122 ppm). The total phenolic content ranged from 58.327 ± 0.017 mg GAE/mL in Pengaron, 83.993 ± 0.017 in Aranio, 104.536 ± 0.032 in Mataraman, to 108.646 ± 0.042 in Bati-Bati. Caffeine levels were 123.876 ± 0.331, 139.340 ± 0.238, 175.495 ± 0.715, and 131.833 ± 0.620 mg/serving, respectively. The findings reveal a strong positive relationship between total phenolic content and antioxidant activity, while caffeine content did not consistently align with antioxidant performance. These findings support the significant role of phenolic compounds in determining the antioxidant potential of South Kalimantan’s local coffee beverages. The highest antioxidant activity and phenolic content were observed in coffee beverages made from Coffea liberica beans originating from Bati-Bati, suggesting its superior potential as a functional beverage with health benefits.